The TESS–Keck Survey. XXIV. Outer Giants May Be More Prevalent in the Presence of Inner Small Planets - Judah Van Zandt; Erik A. Petigura; Jack Lubin; Lauren M. Weiss; Emma V. Turtelboom; Tara Fetherolf; Joseph M. Akana Murphy; Ian J. M. Crossfield; Gregory J. Gilbert; Teo Močnik; Natalie M. Batalha; Courtney Dressing; et al. (The Astronomical Journal)
We present the results of the Distant Giants Survey, a 3 yr radial velocity (RV) campaign to search for wide-separation giant planets orbiting Sun-like stars known to host an inner transiting planet. We defined a distant giant (DG) to have a = 1–10 au and ${M}_{p}\sin i=$ 70–4000 M _⊕ = 0.2–12.5 M _J , and required transiting planets to have a < 1 au and R _p = 1–4 R _⊕ . We assembled our sample of 47 stars using a single selection function and observed each star at monthly intervals to obtain ≈30 RV observations per target. The final catalog includes a total of 12 distant companions: four giant planets detected during our survey, two previously known giant planets, and six objects of uncertain disposition identified through RV/astrometric accelerations. Statistically, half of the uncertain objects are planets and the remainder are stars/brown dwarfs. We calculated target-by-target completeness maps to account for missed planets. We found evidence for a moderate enhancement of DGs in the presence of close-in small planets (CSs), P(DG∣CS) = ${31}_{-11}^{+12}$ %, over the field rate of P(DG) = $1{6}_{-2}^{+2} % $ . No enhancement is disfavored ( p ∼ 8%). In contrast to a previous study, we found no evidence that stellar metallicity raises the enhancement of P(DG∣CS) over P(DG). We found evidence that DG companions preferentially accompany shorter-period CS planets and have lower eccentricities than randomly selected giant planets. This points toward a nuanced picture of dynamically cool formation in which giants interact with, but do not disrupt, their inner systems.